Alzheimer’s Disease-models and Current Approaches: A Review (International Journal of Pharmaceutical Sciences and Drug Research, 2026)
Alzheimer's disease (AD) is a complicated CNS disorders that particularly affect the medial temporal lobe and neocortical area of the brain. AD is characterised by the progressive depletion of neurons in the cortical and hippocampal areas of the brain. The main symptoms are memory loss, amnesia, motor disturbance, mood change, and so on. Alzheimer's disease was 1.9% standard in the South Asian region in 2005; between 2020 and 2040, it's expected to reach an estimated 3.6M to 7.5M cases, respectively. Conversely, a pathological condition is characterized by alterations in microtubule stabilization and amyloid beta formation, resulting from increased oxidative stress and mitochondrial damage. Impairment of cerebral ROS formation is associated with brain mitochondrial dysfunction and deregulated signal transduction. The timely acquisition of relevant animal models for drug candidate screening represents a significant obstacle in neurological research and drug discovery. In this review, we have discussed various in vivo animal models which are helpful for neurological studies. In the end, the treatment for Alzheimer's Disease, modifying treatment strategies, is still under extensive research. We discussed various therapeutic targets to modify the treatment strategies and current drug treatment for AD.